La classe ouvrière et la politique : essais d'analyse historique et sociale - Dion, M.; Institut Maurice Thorez; Huard, R.; Lacroix, A.; Moissonnier, M.; Simon, M.; Tartakowski, D.; Wolikow, Serge (Paris : Editions Sociales, 1980)
Bibliotheek François Vercammen
Frans
Monografie